Coral reefs recruitment in stone substrate on Gosong Pramuka, Seribu Islands, Indonesia - MUHAMMAD ZAINUDDIN LUBIS; SRI PUJIYATI; DANIEL S PAMUNGKAS; MUHAMMAD TAUHID; WENANG ANUROGO; HUSNUL KAUSARIAN (Society for Indonesian Biodiversity, 2018)
Lubis MZ, Pujiyati S, Tauhid M, Anurogo W, Kausarian H. 2018. Coral reefs recruitment in stone substrate on Gosong Pramuka, Seribu Islands, Indonesia. Biodiversitas 19: 1451-1458. Gosong Pramuka is a reef distribution area located in the center of the Seribu Islands of Jakarta, Indonesia. This research was conducted from April to June 2015, located within the Gosong Pramuka area, Kepulauan Seribu, Indonesia. This location has 4 observation stations: Exposed I and II and Shielded I and II. Coral reefs identified at the study sites consisted of 95 colonies, with colonies most abundant in Exposure Station I (35 colonies), and in the genus Acropora and Porites. Acropora coral growth is tabulated, branching, digitate and encrusting, and Porites are only sub-massive and massive. The average area obtained from recruiting coral colonies had a range of 25-50 cm2, and the average diameter of coral recruits was 9-12 cm. The results of this research determined the coral health index of the area is 2-3. Based on the CoralWatch method, the coral at the station where the research was conducted is classified as under stress conditions. The value of recalculated coral density obtained in this study was 0.22 colony/m2 at Exposure Station I, 0.11 colony/m2 at Shielded Station I, 0.13 colony/m2 at Exposure Station II, and in 0.11 colony/m2 at Shielded Station II. Temperatures in all four stations range from 30-32°C; this temperature range is within the optimum temperature range for coral growth. The depth at all four stations was in the ranged from 70-98 cm; this indicates the stations where the research was conducted is still within an optimum depth.